The End and the Beginning The Book of My Life - Zur Mühlen, Hermynia (Open Book Publishers, 2010)
First published in Germany in 1929, The End and the Beginning is a lively memoir of a vanished world and of a rebellious young woman's struggle to achieve independence. Born in 1883 into a distinguished and wealthy aristocratic family of the old Austro-Hungarian Empire, Hermynia Zur Mühlen spent much of her childhood traveling in Europe and North Africa with her diplomat father. After five years on her German husband's estate in czarist Russia she broke with both her family and her husband and set out on a precarious career as a professional writer committed to socialism. As well as translating many leading contemporary authors, notably Upton Sinclair, into German, she herself published an impressive number of politically engaged novels, detective stories, short stories, and children's fairy tales. Because of her outspoken opposition to National Socialism, she had to flee her native Austria in 1938 and seek refuge in England, where she died, virtually penniless, in 1951. This revised and corrected translation of Zur Mühlen's memoir-with extensive notes and an essay on the author by Lionel Gossman-will appeal especially to readers interested in women's history, World War I, and the culture and politics of the late nineteenth and early twentieth centuries. Seven free online supplements are also provided, containing additional original material including a selection of newly translated stories by Zur Mühlen, biographical essays by Gossman and a portfolio of images. The Federal Ministry of Education, Art, and Culture, Department of Literature (/BMUKK-Kultur; Literaturabteilung/), Vienna, Austria, has generously contributed towards the publication of this volume.